Bridging Policy and Practice Implementing Roboust Assessment Strategies to Evaluate Critical Thinking in Internal Medicine - Hudebia Allah Buksh, Zia Ullah Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Critical-thinking ability plays a central role in clinical decision-making, particularly during internal medicine rotations where students encounter diverse and complex patient presentations. Modern medical education encourages structured assessment strategies such as OSCEs, Mini-CEX encounters, and case-based evaluations to strengthen diagnostic reasoning. This study explored the effect of these assessment strategies on critical-thinking development among undergraduate medical students. Methodology: A quasi-experimental study was conducted at LUMHS, Jamshoro, from January 2022 to June 2022, including 200 MBBS students (100 from 4th year and 100 from final year). Participants completed a pre-intervention assessment followed by exposure to structured assessment practices during internal medicine rotation. Activities included OSCE stations, Mini-CEX evaluations, and guided case discussions. A post-test was conducted at the end of the rotation. Data were analyzed using SPSS, with significance set at p<0.05. Results: All groups demonstrated significant improvement in critical-thinking scores post-intervention. This can be attributed to the teaching methods that incorporate clinical cases. Final-year students must have scored higher pre and post-intervention scores due to better clinical exposure and possibly greater confidence. For both groups, the improvement made in diagnostic accuracy, clinical reasoning, and reflection- all with clinical reasoning were deemed statistically significant with p<0.05. The greatest improvement was observed in the clinical Internal Medicine cases of pneumonia, sepsis, and acute presentations of the heart. Conclusion: The implementation of structured assessment strategies has a noticeable impact on final year medical students’ critical thinking performance. This reinforces the value of frequent use of OSCEs, and Mini-CEX exercises in the medicine rotation continuum. Such strategies greatly contribute to the honing and reinforcement of clinical judgement and decision making skills. Keywords: Internal medicine, critical thinking, OSCE, Mini-CEX, undergraduate medical education, clinical reasoning, competency-based training